Pat Schroeder : a woman of the House - Lowy, Joan A., 1956- (Women's biography series., 2003)
"The leading feminist in Congress for nearly twenty-five years, Pat Schroeder was elected in 1972. Schroeder's political career began at a time when many congressional committees were still controlled by a southern gerontocracy. She quickly established a reputation for speaking out in support of left-of-center causes that few of her colleagues would take on. Her razor wit and a talent for creating sound bites endeared her to the media (she coined the phrase "the Teflon president" to describe Ronald Reagan). But she proved equally adept at wielding influence in the vanguard of change. As a member of the House Armed Services Committee, she was instrumental in passing legislation to end sexism in the military despite vicious personal attacks following the U.S. Navy Tailhook scandal. She was in the forefront of exposing gender bias in medical research and was an architect of the family leave bill."--Jacket